2018
DOI: 10.1111/jgh.14131
|View full text |Cite
|
Sign up to set email alerts
|

Lessons learnt from the epidemiology of Helicobacter pylori infection in Malaysia: JGHF Marshall and Warren Lecture 2017

Abstract: The study of Helicobacter pylori in Malaysia has given several important insights into the epidemiology of the infection and pathogenesis of disease. Malaysia has a multiracial Asian population with three major Asian races living together-Malay, Chinese, and Indian. Races remain fairly distinct because of a paucity of interracial marriages. The "Racial Cohort Hypothesis" proposes that the infection occurs within racial groups rather than between. As such, the high prevalence among Indians (> 50%) and Chinese (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 40 publications
0
18
0
Order By: Relevance
“…H. pylori is a Gramnegative microaerophilic bacterium affecting >50% of humans worldwide, with a higher prevalence in developing countries [16,17]. A JGHF Marshall and Warren Lecture in 2017 about the epidemiology of H. pylori infection in Malaysia (three major Asian races living together -Malay, Chinese and Indian) reported that the H. pylori prevalence was high in Indians (>50%) and Chinese (40-50%), while a comparatively low prevalence occurred in Malays (10-20%) [18]. Moreover, at the same year, a systematic review and meta-analysis mentioned that the H. pylori infection is highly endemic in East Asian countries, with 54% of prevalence in China, Japan, Taiwan and Korea in 2015 [19].…”
Section: Introductionmentioning
confidence: 99%
“…H. pylori is a Gramnegative microaerophilic bacterium affecting >50% of humans worldwide, with a higher prevalence in developing countries [16,17]. A JGHF Marshall and Warren Lecture in 2017 about the epidemiology of H. pylori infection in Malaysia (three major Asian races living together -Malay, Chinese and Indian) reported that the H. pylori prevalence was high in Indians (>50%) and Chinese (40-50%), while a comparatively low prevalence occurred in Malays (10-20%) [18]. Moreover, at the same year, a systematic review and meta-analysis mentioned that the H. pylori infection is highly endemic in East Asian countries, with 54% of prevalence in China, Japan, Taiwan and Korea in 2015 [19].…”
Section: Introductionmentioning
confidence: 99%
“…Another study on the Iranian population found a pooled prevalence of 54%, with 42% in children concluding that more than half of this population was infected by H. pylori during the last decades [ 108 ]. A study performed in Malaysia, which stratified the population according to races living in this area, concluded that Chinese and Indians have the highest prevalence rate of H. pylori infection (40–50%) compared to 10–20% in native Malays [ 109 ]. Another study performed on children from China pointed out a prevalence of 18.6% [ 110 ].…”
Section: H Pylori Peculiarities In Asiamentioning
confidence: 99%
“…Similar prevalence was also identified by Zhou et al in Chinese schoolchildren aged 7–12 years (24.1%) [ 111 ]. These findings are enigmatic since, despite the increased H. pylori prevalence, Indians, unlike the Chinese, have a much lower gastric cancer incidence of less than 10 per 100,000 per year [ 109 ]. Lapidot et al assessed H. pylori infection and intestinal microbiome in healthy Israeli children aged between 6–9 years and identified 57% of the participants to be positive for H. pylori infection [ 112 ].…”
Section: H Pylori Peculiarities In Asiamentioning
confidence: 99%
“…It is postulated, that these countries were the origin of these ethnicities, which had subsequently passed down the H. pylori infection through generations born in Malaysia, or after their migration to Malaysia. This is further supported by the paucity of interracial marriages, leaving the ethnicities remaining fairly distinct, and encouraged transmission of infection within the racial group (Goh 2018;Pue & Sulaiman 2013). Other causes for the differences in prevalence amongst ethnicities may be attributed to the virulence factors of H. pylori strains, which are distinct to different ethnicities, host susceptibility factors, and (Goh 2018).…”
Section: Clarithromycin Resistancementioning
confidence: 99%
“…This is further supported by the paucity of interracial marriages, leaving the ethnicities remaining fairly distinct, and encouraged transmission of infection within the racial group (Goh 2018;Pue & Sulaiman 2013). Other causes for the differences in prevalence amongst ethnicities may be attributed to the virulence factors of H. pylori strains, which are distinct to different ethnicities, host susceptibility factors, and (Goh 2018). In our study, although we did not show any statistically significant difference between ethnicity and infection, the proportion of infected patients appeared to be highest among Indians.…”
Section: Clarithromycin Resistancementioning
confidence: 99%